2007
DOI: 10.1029/2006jd007926
|View full text |Cite
|
Sign up to set email alerts
|

Observed and simulated vertically resolved optical properties of continental aerosols over southeastern Italy: A closure study

Abstract: [1] A 2.5-year data set of Raman lidar measurements performed in Lecce within the European Aerosol Research Lidar Network and a numerical model are used to characterize continental aerosols over southeast Italy. Continental conditions are selected by means of back trajectories, limiting the data set to cases of advection from the European continent. The model is used to constrain the relevant aerosol microphysical parameters needed to reproduce the altitude-resolved optical properties measured by lidar, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Figure 10a (grey solid line) reveals that total Lr values vary between 20 and 120 sr and are peaked at ∼ =80 sr. These data are in satisfactory accordance with those retrieved by Raman lidar measurements at 351 nm performed in Lecce during 2.5 year measurements, which provided lidar ratios spanning the 5-130 sr range (Barnaba et al, 2007) for air masses advected from north and east-European countries. Figure 10a In conclusion, the above reported analysis indicates that air masses carrying moderately-absorbing (0.8<SSA<1.0 and 20 sr <Lr<120 sr), fine-mode (0.8<η<1.0 and 0.6<g<0.8) particles are advected over south-east Italy and hence over the central Mediterranean basin, from the urban/industrial European countries.…”
Section: Analysis Of Aod Andå Data For All Sectorssupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 10a (grey solid line) reveals that total Lr values vary between 20 and 120 sr and are peaked at ∼ =80 sr. These data are in satisfactory accordance with those retrieved by Raman lidar measurements at 351 nm performed in Lecce during 2.5 year measurements, which provided lidar ratios spanning the 5-130 sr range (Barnaba et al, 2007) for air masses advected from north and east-European countries. Figure 10a In conclusion, the above reported analysis indicates that air masses carrying moderately-absorbing (0.8<SSA<1.0 and 20 sr <Lr<120 sr), fine-mode (0.8<η<1.0 and 0.6<g<0.8) particles are advected over south-east Italy and hence over the central Mediterranean basin, from the urban/industrial European countries.…”
Section: Analysis Of Aod Andå Data For All Sectorssupporting
confidence: 87%
“…According to d ' Almeida et al (1991) and Hess et al (1998), AOD, η, SSA, and g frequency distribution plots indicate that the Sector A aerosol can be considered representative of "continental average aerosol", mostly made of water soluble and a small amount of soot and insoluble components. A closure study between a 2.5-year data set of Raman lidar measurements (performed in Lecce within the European Aerosol Research Lidar Network) and a numerical model, also indicated that rather clean continental aerosols, with watersoluble fine-mode aerosol accounting for 98-99% of the total number of particles, characterized the aerosol load advected over south-east Italy from north and east European countries (Barnaba et al, 2007).…”
Section: Analysis Of Aod Andå Data For All Sectorsmentioning
confidence: 97%
See 1 more Smart Citation
“…All measurements have been performed in a semi-rural site belonging to the Mediterranean area that is a proper site for monitoring variability of aerosol properties in a complete way due to the influence of different air masses, as confirmed also by systematic LIDAR measurements for vertical optical and physical aerosols properties study (Barnaba et al, 2007;Papayannis et al, 2005). In particular seaborne particles both from the Mediterranean itself and transported from the Atlantic Ocean are present, together with dust from Sahara desert and polluted and smoke aerosols mainly from Central and Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally characterized by clean continental aerosols and a mixing of water-soluble and more absorbing particles is evident (Barnaba et al, 2007). …”
Section: Introductionmentioning
confidence: 99%